2021
DOI: 10.1001/jama.2021.10296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Sedation and Ventilator Liberation Protocol vs Usual Care on Duration of Invasive Mechanical Ventilation in Pediatric Intensive Care Units

Abstract: IMPORTANCEThere is limited evidence on the optimal strategy for liberating infants and children from invasive mechanical ventilation in the pediatric intensive care unit.OBJECTIVE To determine if a sedation and ventilator liberation protocol intervention reduces the duration of invasive mechanical ventilation in infants and children anticipated to require prolonged mechanical ventilation. DESIGN, SETTING, AND PARTICIPANTSA pragmatic multicenter, stepped-wedge, cluster randomized clinical trial was conducted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 27 publications
0
39
0
3
Order By: Relevance
“…Protocols driven by bedside providers may identify eligible patients earlier and result in improved clinical outcomes ( 5 , 6 , 8 ). Other PICU liberation initiatives that heavily relied on nonphysician members of the multidisciplinary have also shown safety and efficacy ( 10 , 23 , 24 ). In any improvement strategy, harnessing the skills of the multidisciplinary is likely to be critical.…”
Section: Discussionmentioning
confidence: 99%
“…Protocols driven by bedside providers may identify eligible patients earlier and result in improved clinical outcomes ( 5 , 6 , 8 ). Other PICU liberation initiatives that heavily relied on nonphysician members of the multidisciplinary have also shown safety and efficacy ( 10 , 23 , 24 ). In any improvement strategy, harnessing the skills of the multidisciplinary is likely to be critical.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 2 decades use of nurse-driven sedation protocols has been increasingly reported and evaluated [ 35 38 ]. A recently published study showed a significant reduction of time to successful extubation after implementation of a sedation and ventilator liberation protocol in 18 PICU sites [ 39 ]. However, its clinical importance may be questionable since the median time to extubation would only decrease from 66.2 to 64.8 h after the implementation of the protocol intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, they have emerged as an independent risk factor for the development of pediatric delirium ( 34 ). While not all studies show a reduction in length of mechanical ventilation after implementation of sedation protocols, they do show a decrease in days with pain, withdrawal or delirium ( 35 , 36 ). Use of sedation protocols has been shown to help in reducing use of benzodiazepines, support the interdisciplinary communication in order to set and manage goals of sedation and to lessen the presentation of iatrogenic withdrawal symptoms ( 37 ).…”
Section: Resultsmentioning
confidence: 99%